Experimental Research and Finite Element Analysis on Mechanical Property of SFRC T-Beam - Min Sun; Jiapeng Zhu; Ning Li; C. C. Fu (Advances in Civil Engineering)
Research on mechanical property of SFRC was done through experiments of two SFRC T-beams and one concrete T-beam, while the influences of different volume fractions of steel fibers on integral rigidity, ultimate shear capacity, and the crack distribution characteristics were analyzed. ANSYS finite element software was used to simulate the tests and it was found that there was good conformation between the results of ANSYS simulation and tests. The test results and finite element software simulation both showed that the incorporation of steel fibers in the concrete can increase the integral rigidity and ultimate shear capacity, while partially reducing the propagation of cracks effectively. It was also proved that it is reliable to simulate SFRC T-beam by ANSYS software.